UPAYA UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) DALAM MENANGANI TUBERKULOSIS DI INDONESIA MELALUI PROGRAM COMMUNITY EMPOWERMENT OF PEOPLE AGAINST TUBERCULOSIS(CEPAT)PADA TAHUN (2012-2017) - Sudana Rambi, I Gede Putu Ari; Priadarsini, Ni Wayan Rainy; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The spread of infectious diseases, especially tuberculosis, is one of the current international issues. The spread of this infectious disease has big impact when it threatens the lives of many people, due to high population mobility from one country to another so that the prevalence of this disease is also getting higher, especially in developing countries. As many asx 95% of tuberculosis cases and 98% ofx deaths are caused by tuberculosisx and occur in developing countries, such as Indonesia has high prevalence of viruses that spread domestically. USAID is an independent aid agency of United States Government which is working to end the spread of infectious diseases globally. through the Community program named People Against Tuberculosis Empowerment, in collaboration with the Indonesia Ministry of Health by providing assistance in an effort to deal with the spread of tuberculosis virus especially about the transmission. Keywords: Transnational disease, Tuberculosis, USAID